Intellectual Property Rights and South-North Global Innovation Networks - Giovanni Prarolo; Alireza Naghavi; Maria Comune (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper explores the role of IPR protection in the emergence of R&D linkages from newly emerging economies. Using data from a new survey on Chinese and Indian firms in the ICT sector, we find IPR protection to be key in the engagement of Southern firms in global innovation networks. A complementary exercise uses global bilateral patent data to investigate the location-specificity of IPR enforcement for this phenomenon. We find that a stringent IPR regime in the North (South) discourages (encourage) foreign patenting activities of firms in the South, suggesting that a global convergence of IPRs can stimulate Southern innovation.
Keywords: F2; O1; O3; 330